Incidence of Thrombocytopenia in Pregnant Females - Saba, Nasim; Rashid, Sobia; Ayub, Hina (Indus Journal of Bioscience Research, 2025)
Introduction: Thrombocytopenia or low platelet counts are frequent hematologic findings in pregnancy, possibly affecting both the mother and her fetus. This paper aims to establish its prevalence and determinants among pregnant females in the Department of Gynaecology and Obstetrics, District Headquarter Teaching Hospital/ Gomal Medical College, Dera Ismail Khan, Pakistan. Objectives: To assess the frequency, causes, and outcome of thrombocytopenia in pregnant females in a tertiary Health Care teaching Institute. Materials and Methods: The cross-sectional observational study was conducted at Department of Gynaecology and Obstetrics, District Headquarter Teaching Hospital/ Gomal Medical College, Dera Ismail Khan, Pakistan in the duration from June, 2024 to November, 2024. Subjects: this regimen is for pregnant females between 18 and 45 years of age with thrombocytopenia that was documented to be <150,000/μL. Results of platelet counts, clinical assessment, and complications were also recorded and compared. Results: In 250 participants, 62 (24.8%) had thrombocytopenia. The most common cause of thrombocytopenia was Gestational thrombocytopenia (61.3 %), followed by hypertensive disorders (24.2 %) and immune thrombocytopenia (9.7%). It was evident that complications to both the mother and fetus were considerably more severe in moderate and severe forms of the disease. Conclusion: Pathological thrombocytopenia during pregnancy needs early recognition and management to avoid adverse outcomes.